Combining the tumor abnormal protein test with tests for carcinoembryonic antigens, cancer antigen 15–3, and/or cancer antigen 125 significantly increased their diagnostic sensitivity for breast cancer. Issue 29 (17th July 2020) - Chen, Rui; Jiang, Chaojun; Zhu, Qiannan; You, Sainan; Li, Yan; Li, Shuo; Ding, Lei; Meng, Haojie; Yang, Yuxin; Zha, Xiaoming; Wang, Jue
Abstract: Background: The tumor abnormal protein (TAP) test is used to screen for many cancers, but its use for breast cancer has not been studied. Methods: Tests for carcinoembryonic antigen (CEA), cancer antigen 125 (CA125), cancer antigen 15-3 (CA15-3), and TAP were administered to 261 women with operable benign breast disease and 348 with breast cancer. The cutoff value used for TAP was the mean + 3 standard deviations for benign breast disease patients (275.64 μm 2 ). Sensitivities and specificities of single biomarker tests and combined tests were compared. The combined tests were defined as positive if any single biomarker was positive, and negative otherwise. Results: The single biomarker test sensitivities were similar: CEA, 7.18%; CA125, 4.89%; CA15-3, 7.47%; and TAP, 4.89%. For the combinations TAP + CEA + CA125, TAP + CEA + CA15-3, TAP + CA125 + CA15-3, and TAP + CEA + CA125 + CA15-3, the sensitivities were 16.67%, 17.82%, 16.38%, and 21.84%, respectively, and the specificities were 93.49%, 97.70%, 93.87%, and 92.72%. Conclusions: The 4-test combination showed the highest sensitivity (21.84%) and may be auxiliary used in early screening. TAP + CEA + CA15-3 showed high specificity (97.70%) and so could be used for confirming breast cancer.